Is the Merger Effective for Indonesian Islamic Banks? - Budiantoro, Risanda Alirastra; Rachman, Mohammad Aulia; Tsani, Luthfi Ibnu; Millatina, Afifah Nur; Fatimatuzzahro, Fatimatuzzahro (Share: Jurnal Ekonomi dan Keuangan Islam, 2024)
The low competitiveness of the Islamic banking sector has raised significant concerns within the government regarding the future viability of this financial industry in Indonesia. In response, a merger has been proposed as a strategic policy to strengthen and enhance the Islamic banking framework. This study seeks to assess the effectiveness of the merger strategy involving three state-owned Islamic banks—Bank Syariah Mandiri, BNI Syariah, and BRI Syariah—which have consolidated to form Bank Syariah Indonesia (BSI). The study employs a qualitative exploratory approach, utilizing analytical tools such as the Five Forces Model and SWOT analysis. The findings indicate that the merger strategy has been effective, as the management of the newly established entity has successfully implemented a range of initiatives to enhance the competitiveness of Islamic banking within the financial sector. These initiatives include product differentiation, innovation, a strong emphasis on service quality, institutional strengthening, and a focus on digital business development. The study concludes that the merger represents a positive step for the Indonesian Islamic banking sector. The strategies implemented by BSI may serve as a potential roadmap for other institutions aiming to enhance their competitive standing in the industry.========================================================================================================ABSTRAK – Efektifkah Merger pada Perbankan Syariah di Indonesia? Rendahnya daya saing sektor perbankan syariah menimbulkan kekhawatiran akan keberlangsungan industri keuangan ini di masa depan di Indonesia. Sebagai kebijakan strategis untuk memperkuat dan meningkatkan kerangka kerja perbankan syariah, pemerintah mengusulkan dilakukannya merger terhadap tiga bank syariah milik negara. Penelitian ini bertujuan untuk mengevaluasi efektivitas strategi merger Bank Syariah Mandiri, BNI Syariah, dan BRI Syariah menjadi Bank Syariah Indonesia (BSI). Penelitian ini menggunakan pendekatan kualitatif eksploratif dengan memanfaatkan Five Forces Model dan analisis SWOT sebagai alat analisis. Hasil penelitian menunjukkan efektivitas strategi merger dalam meningkatkan daya saing perbankan syariah. Manajemen BSI dinilai berhasil menerapkan serangkaian strategi pencapaian tujuan organisasi seperti melakukan diferensiasi produk, inovasi, orientasi pada kualitas layanan, penguatan kelembagaan, dan menseriusi pengembangan bisnis digital. Penelitian ini menyimpulkan bahwa strategi merger merupakan langkah positif bagi sektor perbankan syariah di Indonesia dalam meningkatkan daya saingnya di industri perbankan. Hasil ini dapat menjadi panduan potensial bagi lembaga keuangan syariah lain yang ingin menerapkan strategi serupa.